NuFit-6.0: updated global analysis of three-flavor neutrino oscillations - Ivan Esteban; M. C. Gonzalez-Garcia; Michele Maltoni; Ivan Martinez-Soler; João Paulo Pinheiro; Thomas Schwetz (Journal of High Energy Physics)
Abstract We present an updated global analysis of neutrino oscillation data as of September 2024. The parameters θ 12, θ 13, ∆ m 21 2 $$ Δ {m}_{21}^2 $$ , and ∣ ∆ m 3 ℓ 2 ∣ $$ \mid Δ {m}_{3\ell}^2\mid $$ (ℓ = 1, 2) are well-determined with relative precision at 3σ of about 13%, 8%, 15%, and 6%, respectively. The third mixing angle θ 23 still suffers from the octant ambiguity, with no clear indication of whether it is larger or smaller than 45 ° . The determination of the leptonic CP phase δ CP depends on the neutrino mass ordering: for normal ordering the global fit is consistent with CP conservation within 1σ, whereas for inverted ordering CP-violating values of δ CP around 270° are favored against CP conservation at more than 3.6σ. While the present data has in principle 2.5–3σ sensitivity to the neutrino mass ordering, there are different tendencies in the global data that reduce the discrimination power: T2K and NOvA appearance data individually favor normal ordering, but they are more consistent with each other for inverted ordering. Conversely, the joint determination of ∣ ∆ m 3 ℓ 2 ∣ $$ \mid Δ {m}_{3\ell}^2\mid $$ from global disappearance data prefers normal ordering. Altogether, the global fit including long-baseline, reactor and IceCube atmospheric data results into an almost equally good fit for both orderings. Only when the χ 2 table for atmospheric neutrino data from Super-Kamiokande is added to our χ 2, the global fit prefers normal ordering with ∆χ 2 = 6.1. We provide also updated ranges and correlations for the effective parameters sensitive to the absolute neutrino mass from β-decay, neutrinoless double-beta decay, and cosmology.